Serum hs - CRP and hs - Troponin T concentration in patients with chronic coronary artery disease before and after percutaneous coronary intervention - Binh, Ho Anh; Nguyen Ngoc Son, Hoang Van Quy, Đong Van Kien (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Introduction: Coronary artery disease is a prevalent condition today. Biomarkers assist in diagnosis and prognosis during both short-term and long-term evaluations in PCI patients. This study aims to explore the changes in serum hs-CRP and hs-Troponin T concentrations before and after PCI. Method: A total of 97 chronic CAD patients underwent percutaneous coronary intervention at the Department of Emergency and Cardiovascular Intervention - Hue Central Hospital. This was a descriptive and cross-sectional study. Results: The mean hs-CRP level increased from 4.21 ± 6.49 mg/L to 4.61 ± 5.88 mg/L (p=0.6) after PCI. The mean hs-Troponin T concentration rose from 0.072 ± 0.147 ng/mL to 0.077 ± 0.121 ng/mL (p=0.6) after PCI. Conclusion: There is a positive correlation between hs-CRP and hs-Troponin T levels both before (p=0.022 < 0.05; r = 0.232) and after (p=0.04 < 0.05; r = 0.205) PCI, 24 hours post-procedure.